Child Life Specialists' Evaluation of Hospital Playroom Design: A Mixed Method Inquiry. Issue 2 (9th February 2017) - Weinberger, Nanci; Butler, Allison G.; McGee, Beth; Schumacher, Phyllis A.; Brown, Ryan Linn
Abstract: This study uses the expertise of child life specialists to identify which elements support child life goals for hospitalized children. This study can be used to inform those interested in the optimal design of hospital playrooms. Ninety child life specialists were surveyed using a photograph methodology showing five actual child life playrooms from different hospitals. The participants were asked the following: rate each playroom on 14 dimensions; describe what was liked best about each playroom; and finally, rank order the playrooms based on their ability to support child life goals. Findings show that child life specialists were able to detect fine distinctions among hospital playrooms; thus, highlighting the important role that child life specialists can play in the design or modification of these spaces. Notably, using both Likert ratings and open‐response questions, the value of biophilia in child life play spaces, specifically windows, light, and nature themes were revealed. In addition to biophilic attributes, the playrooms rated most favorably were those that contain pleasing color and décor and plenty of open space. Playrooms that promote sensory‐motor and pretend play were also preferred.